Prevalence of Strongyloides stercoralis infection and associated clinical symptoms among schoolchildren living in different altitudes of Amhara National Regional State, northwest Ethiopia. - Tadesse Hailu Jember; Arancha Amor; Endalkachew Nibret; Abaineh Munshea; Maria Flores-Chavez; Thuy-Hu; Jose M Saugar; Agustín Benito; Melaku Anegagrie (Public Library of Science (PLoS), 2022)
Background Strongyloides stercoralis is a parasite that causes strongyloidiasis in humans. It is prevalent in the tropics and sub-tropics where poor sanitation is a common problem. The true prevalence of S. stercoralis in Ethiopia is underestimated due to the lack of a "Gold" standard diagnostic method. Moreover, its prevalence across altitudinal gradient in Amhara Region has not been studied. Methods A cross-sectional study was conducted among 844 schoolchildren in Amhara Region from April to December 2019. A stool sample was collected from each study participant and processed using formol ether concentration technique (FECT), spontaneous tube sedimentation technique (STST), Baermann concentration technique (BCT), agar plate culture (APC) and real-time polymerase chain reaction (RT-PCR). Data were entered using EpiData and analyzed by SPSS version 23 statistical software. Prevalence of S. stercoralis infection was determined using a single diagnostic technique and combination of techniques. Association of clinical variables with S. stercoralis infection was assessed by logistic regression and independent variables with p<0.05 were considered statistically significant. Results Prevalence of soil-transmitted helminths (STHs) and S. mansoni infections was 38.0% and 20.4%, respectively. Among STHs, the prevalence of hookworm infection was 32.8%. Prevalence of S. stercoralis infection was 39.0%, 28.8%, 10.9%, 10.3%, 4.0% and 2.0% by the respective, combinations of the five methods, RT-PCR, APC, BCT, STST and FECT. The highest prevalence rates, 48.2%, 45.0% and 41.1% of S. stercoralis were recorded in the age group of 12-14 years, males and rural dwellers, respectively. Prevalence rates of S. stercoralis infection in highland, semi-highland and lowland areas were 40.4%, 41.8% and 25.9%, respectively. Having abdominal pain (AOR = 2.48; 95% CI:1.65-3.72), cough (AOR = 1.63;95%CI:1.09-2.42), urticaria (AOR = 2.49;95%CI:1.50-4.01) and being malnourished (AOR = 1.44;95%:1.10-2.01) were significantly associated with strongyloidiasis. Conclusion Prevalence of S. stercoralis infection was high and varied across different altitudes in Amhara Region. Some clinical syndromes were found to be significantly associated with S. stercoralis infection. Therefore, proper diagnosis and preventive strategies against S. stercoralis infection are highly recommended to be devised and implemented in Amhara Region.